Enumeration of monosugars' inhibition characteristics on the kinetics of enzymatic hydrolysis of cellulose. (September 2018) - Haldar, Dibyajyoti; Gayen, Kalyan; Sen, Dwaipayan
Graphical abstract: Highlights: Development of kinetic model on enzymatic hydrolysis of cellulose and product inhibition with Michaelis-Menten assumptions. Comparative kinetic assessment of Michaelis-Menten constants for different lignocellulosic derived sugars. Variation in the lignocellulosic sugars is more significant to the process yield compared to substrate concentration. Cellobiose has maximum inhibition while xylose shows the minimum inhibitory effect with cellulase from Trichoderma reesei . Abstract: A kinetic model based on Michaelis-Menten assumptions is developed here for enzymatic hydrolysis of cellulose using cellulase enzyme derived from Trichoderma reesei . Further, to assess the inhibition of enzyme and the nature of inhibition by different sugars (glucose, galactose, mannose, xylose and cellobiose) the primary kinetic model is modified with the inhibition kinetics. The enzymatic reaction was carried out at pH = 4.8, temperature = 50 °C, solid loading of 1:20 and at 100 rpm stirrer speed. It was observed among all the sugars, only xylose (five carbon sugars) showed non-competitive inhibition with Ki  = 27.2 mM and Vmax  = 0.19 g L −1 h −1 . Glucose and cellobiose manifested competitive inhibition with almost comparable inhibition constants (Ki ) of 24.7 and 26.3 mM respectively, while Vmax  = 0.26 g L −1 h −1 . On the contrary, with galactose and mannose, the inhibition constants decrease to 10.9 and 11.1 mM respectively. Statistical analysis shows that cellobiose attributes to a maximum inhibition with 72% reduction in reducing sugar production. On the contrary, the minimum inhibitory effect with 11% reduction in sugar production was observed with xylose. At the end, ANOVA analysis manifests that the effect of different sugars are much significant in inhibiting the enzyme compared to the substrate concentration in case with the cellulase enzyme from Trichoderma reesei .